Promoting Tourism of Semarang City and Semarang Regency through Game Technology - Lidya Oktorina Kusuma Sakti; Brenda Chandrawati (SISFORMA, 2015)
Semarang is the capital city of Central Java province that has many tourist Attractions. In addition to Semarang, there is Ungaran, the capital city of Semarang Regency which covers the areas of Ungaran and Ambarawa that also has various tourist attractions which attract domestic tourists. But the results of data collection through library study and questionnaire show that object of attractions in Semarang City and Semarang Regency are known only by few tourists. One of the factors that causes tourists’ unfamiliarity with tourism attractions in Semarang City and Semarang Regency is the lack of tourism promotion in the form of media technology. Based on the above facts and considering the opportunities offered by technology which is increasingly recognized by the community, surveyors laid out a game that can be used as one of promotional media of tourism in Semarang City and Semarang Regency. This game will be designed by displaying a map of tours and tourist information in Semarang City and Semarang Regency